THE EFFECT OF LEUCITE MINERAL AND POTASSIUM SOLUBILIZING BACTERIA ON THE POTASSIUM AVAILABILITY IN SOIL, POTASSIUM UPTAKE AND PLANT GROWTH OF TOBACCO (Nicotiana tabacum) BESUKI NA-OOGST - Tri Candra Setyawati; Widya Irawati; Sugeng Winarso (UPT Penerbitan Universitas Jember, 2017)
Tobacco (Nicotiana tabacum) is a plantation crop as a raw material for making cigarettes. Thequality of cigarettes depends on tobacco leaves as raw materials and the fuel is affected by thepotassium content in plant tissues. So that, potassium affects the quality of the leaves.Potassium is absorbed by plants that come from several sources of chemical fertilizers andpotassium mineral that can be found in nature. In this study, besides the addition of leucitemineral as a source of potassium is also done the addition of potassium-solubilizing bacteria toincrease the availability of potassium in the soil and accelerate the process of dissolvingpotassium in the soil. Potassium-solubilizing bacteria (PSB) can accelerate the solubilizing ofpotassium into K+ ions so that more is available in soil and plants are able to uptake potassiumin large quantities. This study used Factorial Randomize Complete Block Design which included4 levels of potassium and 3 levels of PSB with three replications. The purpose of this researchis to know the effect of leucite and PSB in increasing the availability of potassium in the soil,potassium concentration in plant tissue, potassium uptake and plant growth of Besuki NaOogst tobacco. The results showed that the interaction between the addition of potassiumsource and inoculation of potassium-solubilizing bacteria had a significant effect on potassiumavailability in soil, potassium concentration in plant tissue, potassium uptake and a height ofthe plant. The interaction between the leucite rocks and PSB may increase the availability ofpotassium in the soil and give the same results compared with the addition of KNO3 fertilizer.